Pengaruh Bauran Promosi Terhadap Penerimaan Mahasiswa Baru Pada STIE Jayakarta - Loeky Rono Pradopo (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Promotion costs are a factor that is thought to be relative in influencing the acceptance of new students at STIE Jayakarta. To prove the influence of both, research was carried out with the aim of analyzing the influence of promotional costs on new student admissions. The research was conducted at STIE Jayakarta by taking data on promotional costs incurred over the last 10 years. The research was carried out quantitatively, namely with descriptive and inferential analysis. Multiple linear regression was used as an analysis tool while hypothesis testing was carried out using the t test and F test. The research produced three main findings which were in accordance with the proposed hypothesis, namely 1.0media websites had a negative influence on new student acceptance. 2) advertising has a positive influence on new student acceptance. 3) Information Services have a negative influence on new student admissions. Based on these findings, to increase new student acceptance, it is recommended that promotion costs be increased